Migrant Domestic Workers in Europe: the Need for a Better Protection - Tyc, Aneta (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2017)
Migrant domestic workers are estimated at approximately 11.5 million persons worldwide. European women are being replaced in their household chores by immigrant women, e.g. from Africa, Asia and Eastern Europe. The paper focuses on human labour rights of domestic migrant workers, especially from the point of view of the typology which divides international standards concerning labour as a matter of human rights into four groups: rights relating to employment (eg. the prohibition of slavery and forced labour); rights deriving from employment (eg. the right to social security, the right to just and favourable conditions of work); rights concerning equal treatment and nondiscrimination, and instrumental rights (eg. the right to organise, the right to strike). The aim of this paper is to reveal insufficient effectiveness of human labour rights according to the above-mentioned typology. Thus, the author will concentrate on the issues of modern slavery, hyper-precarity and discrimination.